Development of Pictured Storybooks Based on Culture Nusantara to Include Character Values in Students Class III of Muhammadiyah 12 Elementary School Medan - Mazda Lifah Hasibuan (Berpusi Publishing, 2026)
This study aims to develop a picture story book based on Nusantara culture to instill character values in third-grade students of Muhammadiyah 12 Elementary School, Medan. The background of this study is the low understanding of students towards character values and the lack of use of interesting and contextual learning media. Picture story books were chosen as a solution because they are able to combine simple text with interesting visual illustrations so that they are in accordance with the characteristics of elementary school students who are at the concrete operational stage. This study uses the Research and Development (R&D) method with a 4D development model that includes the define, design, develop, and disseminate stages (limited to the develop stage). The instruments used were validation questionnaires by media experts, linguists, and material experts, as well as teacher and student response questionnaires to measure the practicality of the product. The product developed is a picture story book based on the legend of Lake Toba which contains character values such as honesty, responsibility, and discipline. The results of the study show that the developed media has a very high level of validity, with a validation percentage of media experts of 95%, linguists 96%, and material experts 92%. Furthermore, the results of the practicality test showed that the media was highly practical, with a teacher response rate of 96% and a student response rate of 89%. Therefore, the developed picture storybook based on Nusantara culture was declared valid and practical, making it suitable for use as a learning medium to instill character values and increase reading interest in elementary school students.